2012
DOI: 10.1007/s00405-012-2218-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hearing result using Kurz titanium ossicular implants

Abstract: Titanium implants in middle ear surgery were introduced in the late 90s and are now frequently used in middle ear surgery. However, long-term studies of patient outcome are few and have only been published in subgroups of patients. We report the long-term effect of titanium middle ear implants for ossicular reconstruction in chronic ear disease investigated in a Norwegian tertiary otological referral centre. Retrospective chart reviews were performed for procedures involving 76 titanium implants between 2000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
6
20
1
Order By: Relevance
“…This is comparable to similar follow‐up investigations . The patients in this study achieved an ABG of less than 20 dB, which is a common goal for successful hearing improvement …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is comparable to similar follow‐up investigations . The patients in this study achieved an ABG of less than 20 dB, which is a common goal for successful hearing improvement …”
Section: Discussionsupporting
confidence: 87%
“…For ossiculoplasty with a PORP, recently published studies have reported various mean improvements in ABG, including 8.9 dB (standard deviation [SD] 10.3 dB; n = 47), 10 13 dB (SD 13 dB; n = 44), 11 and 14.2 dB (SD 15.3 dB; n = 52). 12 In the present study population, the ABG improved by 8.5 dB (n = 141), which is slightly lower compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One or all of these factors can have implications in the use of ossicular prostheses, extrusions and middle ear sound conduction. Similar hearing outcomes have been observed in other studies on type 3 ossicular reconstruction using titanium prostheses [16,20,21].…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…Different materials are used for ossiculoplasty, including homologous materials (ossicules, cartilage) and synthetic materials (plastipore, ceravital, hydroxyapatite, metal, titanium) 1 2 . Titanium has many advantages in terms of biocompatibility, weight and acoustic performance 3-5 . It is also compatible with MRI at 1.5 and 3 tesla 6 7 , which is of primary importance, especially in cholesteatoma surgery.…”
Section: Introductionmentioning
confidence: 99%